Morphologic alterations in the trachea and the salivary gland following the induction of rapid synchronous vitamin A deficiency in rats - M. A. Anzano (2018)
The use of the synchronous induction method enables both assessment of the sequence and reliability of the appearance of morphologic signs of vitamin A deficiency, and their accurate correlation with biochemical and physiologic abnormalities. In the trachea, hyperplasia of basal epithelial cells was observed by day 4 (T 4 ) following the withdrawal of retinoic acid from retinoate-cycled, stringently deficient rats. Keratinization was observed by day 6, the upper part of the trachea showing the highest incidence of keratinization. All such metaplastic changes originated in the narrow strip of tissue directly cojoining the esophagus. In the submaxillary glands, atrophy of the acini, an increase in interlobular spaces, and fibrosis and dilatation of the ducts was observed by day 10. In more advanced stages of deficiency (T 14 -T 18 ), cyst formation associated with suppuration and extensive cell atrophy was observed. Morphologic changes were less marked in the sublingual glands, although mucin levels were noticeably depressed by day 12 of deficiency. Following the oral dosing of deficient animals (T 12 ) with 350 μg retinyl palmitate, all such changes were reversed within 6 days in the trachea and within 10 days in the submaxillary and sublingual glands. Similar patterns were observed whether animals were force-fed or were fed ad libitum. Apart, therefore, from cause-effect considerations per se, morphologic changes are also potentially valuable reference indicators of deficiency, particularly in time course studies, or where force-feeding attenuates other signs of deficiency.